2007
DOI: 10.1093/jnci/djm060
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Learning Curve for Prostate Cancer Control After Radical Prostatectomy

Abstract: As a surgeon's experience increases, cancer control after radical prostatectomy improves, presumably because of improved surgical technique. Further research is needed to examine the specific techniques used by experienced surgeons that are associated with improved outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
229
5
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 366 publications
(251 citation statements)
references
References 19 publications
10
229
5
6
Order By: Relevance
“…Previous publications have demonstrated that surgical experience and surgical technique affect biochemical recurrence, continence, and potency after RP. [5][6][7] Therefore, these results and the nomogram developed based on these results may not be applicable to other surgeons and await validation using other datasets. In addition, all of the procedures were performed using an open technique and thus these outcomes may not be applicable to patients treated with perineal, laparoscopic, or roboticassisted laparoscopic RP.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have demonstrated that surgical experience and surgical technique affect biochemical recurrence, continence, and potency after RP. [5][6][7] Therefore, these results and the nomogram developed based on these results may not be applicable to other surgeons and await validation using other datasets. In addition, all of the procedures were performed using an open technique and thus these outcomes may not be applicable to patients treated with perineal, laparoscopic, or roboticassisted laparoscopic RP.…”
Section: Discussionmentioning
confidence: 99%
“…Only the series of Vickers et al 20 clearly identifies that the learning curve to decrease prostate cancer recurrence after open radical prostatectomy was significant and did not start to plateau until a surgeon had completed approximately 250 operations.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient population underwent RP at a tertiary care center and all surgeons had extensive experience in performing RP. As surgeon experience has been shown to be an important factor influencing BCR-free survival, 29 our nomogram may predict an overly optimistic chance of recurrencefree survival for patients who are operated on by less experienced surgeons.…”
Section: Discussionmentioning
confidence: 99%